Collaborative Information Retrieval (CIR) - Fidel, Raya; Bruce, Harry; Pejtersen, Annelise Mark; Dumais, Susan; Grudin, Jonathan; Poltrock, Steven (The New Review of Information Behaviour Research, 2000)
The Collaborative Information Retrieval (CIR) Project is designed to study situations where members of a work-team are seeking, searching, and using information collaboratively. Although no research project has addressed this situation before, it is clear from the literature that CIR has already manifested itself in various settings. The Cognitive Work Analysis framework will guide this field study, which will employ observation and interviews with four work-teams from the knowledge industry. The framework examines social, organization, cognitive, and individual characteristics of information seekers, and will be focused to address collaborative situations. The study considers information seeking as a social, dynamic process and has the potential to bring new insights and ideas to the area of information behavior.